2021
DOI: 10.1177/2325967121995803
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Prognostic Factors in Patients With Recurrent Patellar Lateral Dislocation Treated With Isolated Medial Patellofemoral Ligament Reconstruction: A Retrospective Single-Center Analysis

Abstract: Background: Medial patellofemoral ligament reconstruction (MPFLR) is widely used to treat patellofemoral instability. However, it is still unclear when a concomitant bony procedure is needed. Purpose: To evaluate the therapeutic efficacy of isolated MPFLR for recurrent patellar lateral dislocation and to identify the prognostic factors for clinical outcomes. Study Design: Case series; Level of evidence, 4. Methods: A total of 237 patients who had undergone unilateral isolated MPFLR between January 2011 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Although failure risk was not associated with radiographic features (patellar height, trochlear dysplasia, TT-TG distance, patellar tilt), the presence of a preoperative J-sign was associated with a 3-fold increased risk of postoperative instability. The authors also found a significant association between a J-sign and both a CDI value of ≥1.2 and trochlear dysplasia 50 . Similarly, Sappey-Marinier et al reported that the presence of a preoperative J-sign or CDI ≥1.3 was predictive of failure, although no correlation was found between these 2 predictors 51 .…”
Section: Risk Factors Of Recurrent Instabilitymentioning
confidence: 80%
See 1 more Smart Citation
“…Although failure risk was not associated with radiographic features (patellar height, trochlear dysplasia, TT-TG distance, patellar tilt), the presence of a preoperative J-sign was associated with a 3-fold increased risk of postoperative instability. The authors also found a significant association between a J-sign and both a CDI value of ≥1.2 and trochlear dysplasia 50 . Similarly, Sappey-Marinier et al reported that the presence of a preoperative J-sign or CDI ≥1.3 was predictive of failure, although no correlation was found between these 2 predictors 51 .…”
Section: Risk Factors Of Recurrent Instabilitymentioning
confidence: 80%
“…Patellar dislocation recurrence may occur after surgical stabilization. In an analysis of 237 patients who underwent unilateral isolated MPFL reconstruction, Zhao et al aimed to identify factors associated with recurrent lateral PI 50 . Although all included patients demonstrated clinical improvements in Kujala and International Knee Documentation Committee scores, 20 patients (8.4%) experienced some type of failure (redislocation or subjective instability) up to 5 years postoperatively.…”
Section: Risk Factors Of Recurrent Instabilitymentioning
confidence: 99%
“…One study was published in 2022, 17 5 studies were published in 2021, 12,15,27,41,48 3 studies were published in 2020, 2,37,47 2 studies were published in 2019, 8,26 1 in 2017, 22 and 1 in 2014 21 ; 7 studies were judged to be of level 3 evidence, 2,12,15,21,27,37,47 and 6 studies had level 4 evidence. 8,17,22,26,41,48 The mean age of the overall cohort in the 13 studies was 24.1 years, and the mean follow-up was 3.8 years. Within the included studies, 386 patients (406 knees) had a TT-TG >20 mm; of these patients, 276 had undergone MPFLR+TTO, and 110 had undergone iMPFLR.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used the Caton-Deschamps index, yy with the exception of Sisa ´k et al 37 and Matsushita et al, 22 who used the Insall-Salvati ratio. TT-TG was measured using magnetic resonance imaging 2,8,12,17,37 or computed tomography 15,21,22,26,27,41,47,48 axial superimposed images. The studies used variations of the technique used by Matsushita et al, 22 who employed Photoshop software (Adobe, Inc) to superimpose an image of a line going through the deepest point of the trochlear groove to an image of a line though the center of the tibial tuberosity perpendicular to the posterior condylar line and measured the distance between the 2.…”
Section: Imaging Datamentioning
confidence: 99%
“…This difference in findings might be due to the inclusion of TTO in the current treatment strategy. In comparison, studies applying modern MPFL-R - regardless of pathoanatomic features of treated knees - redislocation and/or subluxation rates between 3.4% and 8.4% [ 18 , 43 ] have been seen. One of the few other studies reporting both on luxation and subluxation rates after MPFL-R with/without TTO is that by Enderlein et al [ 15 ].…”
Section: Discussionmentioning
confidence: 99%